Clinical Correlations Delirium and other Comorbid in Elderly with COVID-19 Infection - Khoirun Mukhsinin Putra; Nur Riviati; Djunaidi AR (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background. Delirium is a common condition in geriatric patients. One of the trigger factors for this condition is an infection, such as COVID-19 infection. Elderly with COVID-19 show atypical symptoms such as delirium. Elderly patients with COVID-19 who present with delirium, either as a primary symptom or showing symptoms or signs, have a poor prognosis. This study were aimed to presents covid-19 elderly patient with comorbid delirium. Case presentation. A 77-year-old woman with disorientation for one day came to Emergency Department with her family. She had no history of headaches, blurred vision, or seizures. However, she had a fever, did not want to eat for three days, and had a purulent decubitus ulcer. The patient was diagnosed with acute delirium syndrome, confirmed COVID-19 with sepsis, malnutrition, hypercoagulation, grade III decubitus ulcer, suspected dementia, immobilization, total dependence. The patient admitted to the isolation ward. The patient had meropenem 500 mg every 12 hours, anticoagulants and favipiravir according to the dose and parenteral nutrition. Conclusion. Patients with COVID-19 who present with delirium, either as a primary symptom or presenting symptoms or signs, have a worse outcome. Delirium relationship with comorbid factors can increase mortality and morbidity in the elderly with COVID-19.